The Implementation of The Think-Pair-Share (TPS) Learning Model to Improve Learning Outcomes of Forearm Passing in Fifth Grade Students at SD Negeri 03 Pondok Ranggon, East Jakarta - Tiara Agustina; Hasan Basri (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of the Think-Pair-Share (TPS) learning model in improving forearm passing skills among fifth-grade students at Public Elementary School 03 Pondok Ranggon, East Jakarta. The research utilized a quantitative approach with a quasi-experimental design involving one group pre-test and post-test. A total of 30 students participated as research subjects. The instrument employed was a volleyball forearm passing performance test, which had been validated for its reliability and relevance to the learning objectives. Data were analyzed using descriptive statistics and paired sample t-test to measure the significance of improvement before and after the implementation of the TPS model. The findings revealed a significant increase in students’ forearm passing performance after the intervention. The average post-test scores showed marked improvement compared to the pre-test results, indicating the effectiveness of the TPS model in motor skill learning. The TPS strategy promoted meaningful student engagement, peer interaction, and deeper understanding of skill execution through structured collaboration. These results support the application of student-centered learning models, such as TPS, in physical education to foster both cognitive and psychomotor learning outcomes. This research suggests that implementing the TPS model can be a practical and impactful approach to enhancing volleyball skill acquisition in elementary school physical education settings.